Elastoresistivity of Heavily Hole-Doped 122 Iron Pnictide Superconductors - Hong, Xiaochen; Sykora, Steffen; Caglieris, Federico; Behnami, Mahdi; Morozov, Igor; Aswartham, Saicharan; Grinenko, Vadim; Kihou, Kunihiro; Lee, Chul-Ho; Büchner, Bernd; Hess, Christian (Frontiers in Physics, 2022)
Nematicity in the heavily hole-doped iron pnictide superconductors remains controversial. Sizeable nematic fluctuations and even nematic orders far from a magnetic instability were declared in RbFe2As2 and its sister compounds. Here we report a systematic elastoresistance study of series of isovalent- and electron-doped KFe2As2 crystals. We found divergent elastoresistance upon cooling for all the crystals along their [110] direction. The amplitude of elastoresistivity diverges if K is substituted with larger ions or if the system is driven towards a Lifshitz transition. However, we conclude none of them necessarily indicates an independent nematic critical point. Instead, the increased nematicity can be associated with another electronic criticality. In particular, we propose a mechanism how elastoresistivity is enhanced at a Lifshitz transition.